English Department Students’ Attitudes Toward the Use of English Slang on X (Twitter) - Nadia Rahma; Masitha Achmad Syukri (Qoumun: Jurnal Pengabdian Masyarakat, 2026)
Purpose of the study: This study investigates the language attitudes of English Department students at Universitas Airlangga toward the use of English slang on X (Twitter). Methodology: A qualitative approach was employed using Baker’s (1992) language attitudes theory and Crystal’s (2004) internet language theory. Data were collected from 30 English Department students through an open-ended questionnaire and semi-structured interviews, and analyzed thematically. Main Findings: Three themes emerged positive, negative, and neutral attitudes. Most students showed positive attitudes, perceiving English slang on X as offering communicative benefits, while some also reported communicative barriers. Novelty/Originality of this study: This study is the first to specifically examine English Department students’ attitudes toward English slang use on X, bridging the gap between studies on learners’ general language attitudes and studies on slang attitudes among non-learner social media users.